Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems 2017
DOI: 10.1145/3025453.3025603
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Touchscreen and Mouse Input Performance by People With and Without Upper Body Motor Impairments

Abstract: Controlled studies of touchscreen input performance for users with upper body motor impairments remain relatively sparse. To address this gap, we present a controlled lab study of mouse vs. touchscreen performance with 32 participants (16 with upper body motor impairments and 16 without). Our study examines: (1) how touch input compares to an indirect pointing device (a mouse); (2) how performance compares across a range of standard interaction techniques; and (3) how these answers differ for users with and wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 19 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Irwin et al [61] investigated the use of touchscreen technology by people with gross motor impairments and found that this group exhibits longer dwell times compared to those without. When touchscreen input was compared with mouse input, Findlater et al [35] found that though touchscreen input was faster for people with motor impairments, it also led to a three-fold increase in pointing (tapping) errors on the touchscreen compared to the mouse. Some approaches to address these problems have used the edge of the screen to stabilize gestures [38,140], or a swiping ("swabbing") interaction rather than tapping, which allows the user to stabilize their finger on the screen itself [135].…”
Section: Accessible Mobile Computingmentioning
confidence: 99%
See 4 more Smart Citations
“…Irwin et al [61] investigated the use of touchscreen technology by people with gross motor impairments and found that this group exhibits longer dwell times compared to those without. When touchscreen input was compared with mouse input, Findlater et al [35] found that though touchscreen input was faster for people with motor impairments, it also led to a three-fold increase in pointing (tapping) errors on the touchscreen compared to the mouse. Some approaches to address these problems have used the edge of the screen to stabilize gestures [38,140], or a swiping ("swabbing") interaction rather than tapping, which allows the user to stabilize their finger on the screen itself [135].…”
Section: Accessible Mobile Computingmentioning
confidence: 99%
“…But, very few gestures were created on the skin. The wider space of non-touchscreen locations in some cases relieved the need for precise input with small targets, a known problem for users with motor impairments (e.g., [35]).…”
Section: Non-touchscreen Taskmentioning
confidence: 99%
See 3 more Smart Citations